A three-dimensional biomechanical analysis of the squat during varying stance widths - Escamilla, R. F.; Fleisig, G. S.; Lowry, T. M.; Barrentine, S. W.; Andrews, J. R. (Medicine & Science in Sports & Exercise, 2001)
Purpose: The purpose of this study was to quantify biomechanical parameters employing two-dimensional (2-D) and three-dimensional (3-D) analyses while performing the squat with varying stance widths. Methods: Two 60-Hz cameras recorded 39 lifters during a national powerlifting championship. Stance width was normalized by shoulder width (SW), and three stance groups were defined: 1) narrow stance squat (NS), 107 +/- 10% SW; 2) medium stance squat (MS), 142 +/- 12% SW; and 3) wide stance squat (WS), 169 +/- 12% SW. Results: Most biomechanical differences among the three stance groups and between 2-D and 3-D analyses occurred between the NS and WS. Compared with the NS at 45 degrees and 90 degrees knee flexion angle (KF), the hips flexed 6-11 degrees more and the thighs were 7-12 degrees more horizontal during the MS and WS. Compared with the NS at 90 degrees and maximum KF, the shanks were 5-9 degrees more vertical and the feet were turned out 6 degrees more during the WS. No significant differences occurred in trunk positions. Hip and thigh angles were 3-13 degrees less in 2-D compared with 3-D analyses. Ankle plantar flexor (10-51 N.m), knee extensor (359-573 N.m), and hip extensor (275-577 N.m) net muscle moments were generated for the NS, whereas ankle dorsiflexor (34-284 N.m), knee extensor (447-756 N.m), and hip extensor (382-628 N.m) net muscle moments were generated for the MS and WS. Significant differences in ankle and knee moment arms between 2-D and 3-D analyses were 7-9 cm during the NS, 12-14 cm during the MS, and 16-18 cm during the WS. Conclusions: Ankle plantar flexor net muscle moments were generated during the NS, ankle dorsiflexor net muscle moments were produced during the MS and WS, and knee and hip moments were greater during the WS compared with the NS. A 3-D biomechanical analysis of the squat is more accurate than a 2-D biomechanical analysis, especially during the WS.